Analisis Campuran Limbah Daun Gamal, Daun Lamtoro, dan Kulit Pisang sebagai Pakan Alternatif Udang - Shafwan Amrullah; Cyrilla Octaviananda; Icha Ramadhani (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), 2023)
The waste of several organic materials in several areas in West Nusa Tenggara continues to increase. One of the most commonly found is banana peel waste, lamtoro leaf waste, and gamal leaf waste. One alternative to reduce this waste, can be converted into alternative shrimp feed. The advantage of using these ingredients is the vegetable protein content which is equivalent to sea fish. In this study, researchers carried out the process of making shrimp feed using gamal leaf waste, lamtoro leaves and banana peels. The research treatments used a variety of raw material mixtures, namely Formula 1, Formula 2 and Formula 3. The quality indicators tested in this study were moisture content, ash content, crude protein. The results showed a decrease in water content from 22.96%-15.86% from formula 1 to formula 3. The ash content increased from 4.8% to 9% from formula 1 to 3. Meanwhile, the crude protein content increased from 5.9% to 8.48% from formulas 1 to 3. Based on the three formulas, it can be concluded that formula 3 can be said to be the best with a mixture of 500 grams of gamal, 150 grams of lamtoro leaves, 150 grams of fine bran, 100 grams of corn flour, tapioca flour 30 grams, 20 grams of EM4 and 50 grams of banana peel. Based on these results it can also be concluded that the waste obtained from the remaining banana peels, gamal and lamtoro can be made into more useful shrimp feed.